Experimental detection of liquid-phase OH radical decay originating from atmospheric-pressure plasma exposure. (29th April 2021) - Takeda, Kazuki; Sasaki, Shota; Luo, Wencheng; Takashima, Keisuke; Kaneko, Toshiro
Abstract: Breaking-through methods for experimental observation on short-lived reactive species in the liquid phase, generated at the interface of atmospheric-pressure plasmas (APPs), can contribute greatly to an understanding of the reaction processes. A newly developed high-speed liquid flow interface in helium plasma transports APP-generated liquid-phase OH radical (·OH) by advection, enabling observation of rapid APP-generated ·OH decay within approximately 0.5 ms for the first time, to our best knowledge. This experimental detection and the deduced quantification of the rapid ·OH decay suggests a surface localization of ·OH, and thus can be an important finding to characterize the inhomogeneous ·OH distribution.